2003
DOI: 10.1093/emboj/cdg090
|View full text |Cite
|
Sign up to set email alerts
|

Tim50, a novel component of the TIM23 preprotein translocase of mitochondria

Abstract: The preprotein translocase of the inner membrane of mitochondria (TIM23 complex) is the main entry gate for proteins of the matrix and the inner membrane. We isolated the TIM23 complex of Neurospora crassa. Besides Tim23 and Tim17, it contained a novel component, referred to as Tim50. Tim50 spans the inner membrane with a single transmembrane segment and exposes a large hydrophilic domain in the intermembrane space. Tim50 is essential for viability of yeast. Mitochondria from cells depleted of Tim50 displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
146
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(152 citation statements)
references
References 51 publications
(49 reference statements)
4
146
0
2
Order By: Relevance
“…Saturation of mouse liver mitochondria TOM and TIM23 complexes with cold SU9-DHFR (dihydrofolate reductase) and B2Δ19-DHFR inhibited in a dose-dependent manner the import of 35 S-Met-labeled SU9-DHFR 23,[32][33][34][35] used throughout this work as a positive control (Supplementary Figure 2A). This inhibition was even more pronounced when cold SU9-DHFR and B2Δ19-DHFR were stabilized with methotrexate (MTX) 23 (Supplementary Figure 2B). However, SU9-DHFR did not inhibit GB import, while B2Δ19 did so to a minor level at the highest dose (Supplementary Figure 2C); however, MTX stabilization completely prevented B2Δ19-DHFR inhibition of GB import (Supplementary Figure 2D).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Saturation of mouse liver mitochondria TOM and TIM23 complexes with cold SU9-DHFR (dihydrofolate reductase) and B2Δ19-DHFR inhibited in a dose-dependent manner the import of 35 S-Met-labeled SU9-DHFR 23,[32][33][34][35] used throughout this work as a positive control (Supplementary Figure 2A). This inhibition was even more pronounced when cold SU9-DHFR and B2Δ19-DHFR were stabilized with methotrexate (MTX) 23 (Supplementary Figure 2B). However, SU9-DHFR did not inhibit GB import, while B2Δ19 did so to a minor level at the highest dose (Supplementary Figure 2C); however, MTX stabilization completely prevented B2Δ19-DHFR inhibition of GB import (Supplementary Figure 2D).…”
Section: Resultsmentioning
confidence: 97%
“…The mitochondrial nucleoid encodes only for 13 structural proteins, while the rest of the mitochondrial proteome is nuclear-encoded and transported to the mitochondria through a sophisticated protein import machinery. [19][20][21][22][23][24][25][26][27][28] The translocase of the outer mitochondrial membrane (TOM), the entry gate to the mitochondria, 20 passes on the cargos to the sorting and assembly machinery (SAM) complex, to the mitochondrial intermembrane space assembly (MIA) complex and to the translocases of the inner mitochondrial membrane TIM22 or TIM23 complexes for delivery to the outer membrane, the intermembrane space, the inner membrane or the matrix, respectively. [19][20][21][22]25,26,28 Unexpectedly, we found that GB mitochondrial entry is independent of the TOM-TIM23 complexes, but requires instead the Sam50 and Tim22 channels and mitochondrial heat-shock protein 70 (mtHsp70).…”
mentioning
confidence: 99%
“…At this stage of translocation, no cross-links of translocating precursors to any other TIM23 subunit were observed so far. The topology of Tim50 is also in agreement with such a function as it is integrated into the inner membrane with a single transmembrane domain and exposes a conserved domain into the IMS (Geissler et al, 2002;Yamamoto et al, 2002;Mokranjac et al, 2003a). Using a yeast two-hybrid screen, pulldown experiments and crosslinking the latter domain was shown to bind to the IMS domain of Tim23 (Geissler et al, 2002;Yamamoto et al, 2002;Alder et al, 2008b).…”
Section: Introductionmentioning
confidence: 81%
“…The deletion strain of TIM50 in a diploid W303 background was described before (Mokranjac et al, 2003a). It was transformed with a pVT-U plasmid (Vernet et al, 1987) carrying a full-length wild-type Tim50 and subsequently sporulated to obtain a haploid yeast strain with a chromosomal deletion of TIM50 and a wild-type copy of Tim50 on the URA plasmid.…”
Section: Plasmids Yeast Strains and Cell Growthmentioning
confidence: 99%
See 1 more Smart Citation